Efforts to Improve Learning Achievement by Guidance and Counseling Teachers for Orphan Children - M. Harwansyah Putra Sinaga; Dwi Syahfitri Baskoro; Sarmila Yanti Munthe; Say Azmi (Education Achievement: Journal of Science and Research, 2024)
This research was conducted to see directly the efforts of guidance and counseling teachers in improving the learning achievement of students with orphan status in the Al-Hijrah 2 IT Middle School environment. This research used a qualitative descriptive research method. The research was carried out by collecting data by means of observation, interviews and documentation studies. Where the results of the research were then analyzed using the Miles and Huberman data analysis methods. This research takes as its subject a guidance and counseling teacher who acts as a school counselor. From the research results, it can be seen that guidance and counseling teachers also participate in efforts to improve the learning achievement of orphaned children.